A new Macrostemum Kolenati, 1859, from Western Africa (Trichoptera, Hydropsychidae) - (:unkn) unknown (My University, 2023)
A detailed comparison of the genitalia of Macrostemum distinctum (Ulmer, 1912) from Cameroon with those from West African specimens indicates that the latter belong to a distinct species which is described as Macrostemum statzneri Gibon n. sp. A draft distribution map is presented based on old and unpublished data.
Keywords: African Research